Understanding Classroom Diversity through Enrolment Trends - Negi, Suman (JOURNAL OF INDIAN EDUCATION, 2023)
Diversity refers to the different identities that exist among people, some of the common identity categories that we refer to include caste, religion, gender, race, class, etc. Living in a multicultural country like India the meaning and concept of diversity may subsume an even greater significance. Schools are mini societies, and equally reflect the complexities of difference and diversity visible in society, and school administrators and teachers have to be responsive in maintaining an inclusive school climate and culture so as to maximise from this diversity. With growing mobility amongst people across borders the diversity in the educational settings is also set to increase, further posing its set of challenges. Classroom diversity has never been more than it is today. This heterogeneity that students bring to a classroom needs to be integrated to the overall learning process, rather than visible elements of exclusion and discrimination